Vegetable oils as skin penetration enhancer in topical and transdermal anti-inflammatory formulations: an integrative review (Research, Society and Development, 2021)
This integrative literature review aims to identify which vegetable oils are used as skin permeation promoters in topical and transdermal anti-inflammatory formulations. Medline, Science Direct and BVS databases were used, constituting nineteen studies. The vegetable oils mentioned in the studies were fixed (OF) and essential (EO) oils, including oleic acid, palm kernel oil, palm oil, eucalyptus oil, clove oil, chuanxiong oil, D-limonene oil, olive oil, soybean oil, cinnamon oil, pine oil, castor oil, angelica oil, camellia oil, cyperu oil, Zanthoxylum bungeanum essential oil, basil essential oil, rosemary essential oil. With the results obtained, a concentration range between 0.1% and 10% was evidenced for the skin permeation tests of chemical promoters and also a range of factors that interfered in the percentage of permeation. OE can modify the solvent properties and, consequently, its action on the stratum corneum, significantly altering the partition and diffusion of molecules in the skin tissue. Conventional gel formulations and transdermal microemulsion and nanoemulsion formulations showed a high skin permeation rate reaching up to 99.85% compared to some products already on the market, such as diclofenac, nimesulide and piroxicam gels. From this perspective, based on research and information about the constituents and behavior that vegetable oils have, the data from the articles provide important information that show the promising impact on the permeability of the actives and the consequent increase in the therapeutic effect.